A new VHF doppler radar experiment at Syowa Station, Antarctic - Igarashi, Kiyoshi; Ogawa, Tadahiko; Ose, Masami; Fujii, Ryoichi; Hirasawa, Takeo (1982)
P(論文) A new VHF doppler radar with a minicomputer for real-time processing and radar control will be operational in 1982 at Syowa Station, Antarctica, in order to study E-region irregularities and neutral wind motions. This project, one of the ground-based study programs in Antarctica for the Middle Atmosphere Program (MAP, 1982-1985), aims at clarifying how the middle atmosphere in the 80-110km altitude region behaves in response to the energy flow from the magnetosphere into the polar ionosphere, especially during a substorm. The radar has three operation modes; spectrum mode, double-pulse mode and meteor mode. The spectrum mode provides doppler spectra of back-scattered signals from which characteristics of the plasma turbulence due to auroral activity can be investigated. Mean drift velocities of the irregularities are derived from the double-pulse mode. The drift velocity obtained by this mode ultimately can be related to the ionospheric electric field. In the meteor mode, wind motions in the 80-110km altitudes are investigated by using meteor trails. departmental bulletin paper